Effects of external ankle support on balance control outcomes following muscle fatigue in individuals with ankle instability: A systematic review and meta-analysis - Hanieh KHALILIYAN; Mahmood BAHRAMIZADEH; Amirhossein ZARE; Kavita BATRA; Gabriella NUCERA; Aldo SITIBONDO; Aanuoluwapo AFOLABI; Majid ANSARI; Olayinka ILESANMI; Lukasz SZARPAK; Alireza KHAGHANI; Shahla MOHAJERI; et al. (Journal of Health and Social Sciences)
Introduction: Lateral Ankle sprain is a common sports injury with a high incidence rate after muscle fatigue. Health specialists are searching for the best conservative approach to reduce the complications of this injury and decrease the incidence rate after fatigue. This systematic review and meta-analysis aimed to assess the effectiveness of external ankle support on balance in patients with ankle instability following muscle fatigue. Methods: We conducted a systematic search of PubMed, Scopus, and Web of Science up to April 29, 2024, to find articles involving populations with ankle instability, interventions using external ankle support (taping or ankle orthoses), and outcomes related to balance assessed during muscle fatigue. The Risk of Bias 2 tool was used for risk of bias assessment. Data on patients, interventions, fatigue protocols, and outcomes were extracted and analysed. A meta-analysis was performed using Review Manager 5.3 software, calculating standardized mean differences with 95% confidence intervals (CI) for each outcome. Results: Nine crossover studies involving 230 subjects were included. The narrative synthesis shows that external ankle supports improve the single leg hop test [Mean difference=7.84, P=0.01], center of pressure range and velocity, and ankle inversion. The meta-analysis results indicate that compared to the control group, external ankle supports after muscle fatigue significantly change Y balance clinical test-posterolateral [MD=1.22, 95% CI (0.16, 2.28), p=0.03], Y balance clinical test-posteromedial [Mean difference=2.60, 95% CI (0.42, 4.79), p=0.03], center of pressure time to stabilization-mediolateral [Mean difference=-0.68, 95% CI (-1.29, -0.07), p=0.04], center of pressure time to stabilization-vertical [Mean difference=-0.62, 95% CI (-0.94, -0.30), p=0.01], and vertical ground reaction force [Mean difference=0.58, 95% CI (0.21, 0.96), p=0.02]. Discussion: External ankle supports are an effective conservative intervention for improving specific aspects of balance in patients with ankle instability, particularly following muscle fatigue. Significant improvements were observed in the Y Balance Test, center of pressure measures, vertical ground reaction force, and single-leg hop performance. Healthcare professionals are encouraged to incorporate external ankle supports into rehabilitation programs for individuals with ankle instability. These supports can enhance balance, improve functional outcomes, and help mitigate the negative effects of muscle fatigue on postural stability.